The effect of Ti or Zr additions on the microstructure and magnetic properties of MnAl-C alloys - Feng, Le; Nielsch, Kornelius; Woodcock, Thomas George (Results in Physics, 2021)
As-transformed and hot-deformed samples of MnAl-C alloys with Ti or Zr additions have been produced and characterized using magnetometry, X-ray diffraction, scanning electron microscopy and transmission electron microscopy. Both Ti and Zr additions in MnAl-C alloys form carbide primary phases, TiC and ZrC, which consume the carbon meant to be dissolved in the metastable τ-phase to stabilize it against decomposition. With these two additions, the Curie temperature of τ-phase increases while its stability against decomposition decreases. After hot deformation, the MnAl-C alloys with Ti or Zr additions have lower polarisation and remanence due to the reduced stability of the τ-phase. Adding extra carbon along with Ti to a MnAl-C alloy in order to compensate for the C lost on formation of TiC restored the original stability of the τ-phase. After hot-deformation, this alloy exhibited a lower polarisation and remanence owing to the unexpected formation of the γ2-phase.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Carbide; Hot deformation; Magnetic property; MnAl; Stability